SAINS DATA RAPIDMINER: PENGARUH TEORI DAN PRAKTIK LIS TERHADAP IPLM - Fadhilah, Ridha Dinda (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2024)
The IPLM study aims to evaluate reading habits in Indonesia using indicators of frequency, duration, network access and library style. Access to libraries is difficult due to a lack of sufficient numbers and a shortage of non-fiction books in some areas. Students' understanding of reading is also low. To address this problem, an increase in the number of school and public libraries is needed, as well as stronger family and community education. Literacy programs in schools need further research. Another problem is related to the physical structure of libraries in Indonesia and the decline in book sales. The government is trying to strengthen public literacy, but surveys show only 12% prefer to read physical books. Libraries have an important role in increasing interest in reading and literacy culture. Universities and educational institutions also play an important role. This research uses descriptive quantitative methodology with data collection through questionnaires. By improving libraries, integrating literacy activities, and involving all stakeholders, literacy culture and interest in reading will continue to develop in Indonesia. Keywords : ASEAN; Indonesia; IPLM; Literacy; Library; Habitus Theory